How to cope with stroke: an interventionalist's view - Grunwald, I; Kuehn, A (2011)
Ischemic stroke is a demanding drain on the public health infrastructure and social economics. Clinical efforts in acute stroke now center on rapid restoration of blood flow to salvageable brain tissue, which should minimize brain damage and improve clinical outcomes. Mechanical recanalization devices recently gained successful entry into acute endovascular stroke treatment. The breakthrough of mechanical recanalization, with or without concomitant lysis, is evident as technologies become more refined and sophisticated. Since the first case of mechanical clot removal was reported in 1958, this approach has successfully evolved. Current mechanical trials show great potential of the thrombectomy devices and huge evidence of their ability to rapidly restore blood flow in cases of major cerebral vessel occlusion. The rising interest in this therapy option may be explained by the awareness that only a minority of patients benefit from i.v.-lysis in major vessel occlusion. In addition, i.v.-lysis is limited due to the narrow time window from acute stroke symptom onset to therapy administration. Also, as no adjuvant thrombolytic therapy is needed in mechanical thrombectomy, endovascular devices have great promise to extend the narrow time interval for medical acute ischemic stroke treatment. Mechanical recanalization devices can also be used in patients that are ineligible for i.v. thrombolysis (e.g. previous operation) or where thrombolytic therapy has failed. This review concentrates on giving the reader an assessable insight into current treatment options of acute ischemic stroke and tries to focus on the essentials for setting up an acute stroke service. Advances of mechanical thrombectomy devices and their improved recanalization rates in major intracranial artery occlusions are discussed. The goal of any acute stroke treatment is to minimize brain damage by restoring the blood flow as quickly as possible.